2002
DOI: 10.1159/000048208
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Dopamine D<sub>1</sub> and D<sub>2</sub> Agonists Additively Decreases Daily Food Intake, Body Weight and Hypothalamic Neuropeptide Y Level in Rats

Abstract: This study investigated whether co-administration of dopamine D1 and D2 agonists might additively inhibit the feeding effect and whether this effect was mediated by the action on hypothalamic neuropeptide Y (NPY). The D1 agonist SKF 38393 (SKF) and D2 agonists apomorphine (APO) or quinpirole (QNP) were administered, alone or in combination, to examine this possibility. In single administration, decreases of daily food intake were observed only in rats treated twice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Accordingly, they suggested that a deficiency in the dopaminergic receptor binding promoted overeating to compensate for this lack of dopaminergic activity. Similarly, co-administration of D1 and D2 agonists (i.e., SKF 38393 + apomorphine or quinpirole) was found to result in reduced daily food intake and body weight in rats [36]. Dopamine's effect on food intake also seems to be mediated through its actions within the hypothalamus.…”
Section: Dopaminergic Agentsmentioning
confidence: 90%
“…Accordingly, they suggested that a deficiency in the dopaminergic receptor binding promoted overeating to compensate for this lack of dopaminergic activity. Similarly, co-administration of D1 and D2 agonists (i.e., SKF 38393 + apomorphine or quinpirole) was found to result in reduced daily food intake and body weight in rats [36]. Dopamine's effect on food intake also seems to be mediated through its actions within the hypothalamus.…”
Section: Dopaminergic Agentsmentioning
confidence: 90%
“…DA is one of the most salient neurotransmitters in the reinforcement value of food and the regulation of its intake (Epstein et al, 2002). Although drugs that substantially increase brain DA tend to induce anorexia in animals (eg Bina and Cincotta, 2000;Kuo, 2002), there is considerable variation in response magnitude across human subjects. In a recent study with a small group of obese adults, Leddy et al (2004) found that approximately equal numbers showed either a large decrease, a small/moderate Comparisons between the groups were made using one-way ANOVA for the continuous variables and w 2 tests for the categorical data.…”
Section: Discussionmentioning
confidence: 99%
“…2001). Furthermore, interaction of the DRDs with other factors implicated in obesity, such as neuropeptide Y (NPY), corticotropin releasing hormone (CRH), have been demonstrated (Bina & Cincotta 2000; Kuo 2002). In spite of this evidence, very little is known about the dopamine receptors in cattle with the exception of DRD2 , which has been completely sequenced (Chio et al .…”
Section: Primer Sequences Amplified Fragment Length and Annealing Tementioning
confidence: 99%